2012
DOI: 10.1089/ten.tea.2012.0167
|View full text |Cite|
|
Sign up to set email alerts
|

Embedded Silica Nanoparticles in Poly(Caprolactone) Nanofibrous Scaffolds Enhanced Osteogenic Potential for Bone Tissue Engineering

Abstract: Poly(caprolactone) (PCL) has been frequently considered for bone tissue engineering because of its excellent biocompatibility. A drawback, however, of PCL is its inadequate mechanical strength for bone tissue engineering and its inadequate bioactivity to promote bone tissue regeneration from mesenchymal stem cells. To correct this deficiency, this work investigates the addition of nanoparticles of silica (nSiO(2)) to the scaffold to take advantage of the known bioactivity of silica as an osteogenic material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…In a similar study, the incorporation of bioactive nanoparticles such as silica (SiO 2 ) to electrospun PCL was shown to induce and support osteogenic differentiation of hMSCs. 20 They observed that the addition of silica enhanced ALP activity and up-regulated the production of osteo-related extracellular proteins. 20 Taken together, our results suggest that the addition of nanoclay to PCL scaffolds sustained and enhanced the osteogenic differentiation of seeded hMSCs, when compared to only the PCL.…”
Section: Adhesion and Proliferation Of Hmscs On Nanoclay-enriched Pclmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar study, the incorporation of bioactive nanoparticles such as silica (SiO 2 ) to electrospun PCL was shown to induce and support osteogenic differentiation of hMSCs. 20 They observed that the addition of silica enhanced ALP activity and up-regulated the production of osteo-related extracellular proteins. 20 Taken together, our results suggest that the addition of nanoclay to PCL scaffolds sustained and enhanced the osteogenic differentiation of seeded hMSCs, when compared to only the PCL.…”
Section: Adhesion and Proliferation Of Hmscs On Nanoclay-enriched Pclmentioning
confidence: 99%
“…20 They observed that the addition of silica enhanced ALP activity and up-regulated the production of osteo-related extracellular proteins. 20 Taken together, our results suggest that the addition of nanoclay to PCL scaffolds sustained and enhanced the osteogenic differentiation of seeded hMSCs, when compared to only the PCL. The increase in the hMSCs proliferation rate, followed by the burst in the ALP activity and the subsequent mineralization, are features that are of major importance when aiming at the designing of bioactive matrix for musculoskeletal tissue engineering.…”
Section: Adhesion and Proliferation Of Hmscs On Nanoclay-enriched Pclmentioning
confidence: 99%
See 1 more Smart Citation
“…The osteogenic differentiation was enhanced in human osteoblasts seeded on PCL-rod nHA compared to those on PCL or PCLspherical nHA and provided the optimal niche for differentiation of adipose-derived MSCs. Ganesh et al [2012] recently showed that silica nanoparticles with a size of approximately 10 nm (concentrations of 0.5 and 1% w/v) were enforced within, or attached to, PCL nanofibers. These silica-PCL nanofibers enhanced the osteogenic differentiation of MSCs; however, the inclusion of silica nanoparticles in the culture medium resulted in ingestion followed by cell death [Ganesh et al, 2012].…”
Section: The Role Of Nanoparticles In Osteogenic Differentiationmentioning
confidence: 99%
“…Owing to their large surface area relative to volume, the surface-related properties are dominant, and these include surface reactivity, protein adsorption, and surface degradation, which ultimately control the cellular behaviors. 210,211 Dentin and pulp are one of the most widely explored dental tissues utilizing the nanofibrous scaffolds. Nanofibrous scaffolds can be produced either by phase-separation, electrospinning, or peptide synthesis approach.…”
mentioning
confidence: 99%